The complete genome sequence of Chromobacterium violaceum reveals remarkable and exploitable bacterial adaptability - Ribeiro de Vasconcelos, Ana Tereza; De Almeida, Darcy F.; Hungria, Mariangela; Guimarães, Claudia Teixeira; Antônio, Regina Vasconcellos; Cunha Almeida, Francisca; De Almeida, Luiz G. P.; De Almeida, Rosana; Alves-Gomes, José Antonio; Mazoni Andrade, Elizabeth; Araripe, Julia; De Araújo, Magnolia Fernandes Florencio; et al. (Proceedings of the National Academy of Sciences, 2003)
Chromobacterium violaceum is one of millions of species of free-living microorganisms that populate the soil and water in the extant areas of tropical biodiversity around the world. Its complete genome sequence reveals (i) extensive alternative pathways for energy generation, (ii) ≈500 ORFs for transport-related proteins, (iii) complex and extensive systems for stress adaptation and motility, and (iv) wide-spread utilization of quorum sensing for control of inducible systems, all of which underpin the versatility and adaptability of the organism. The genome also contains extensive but incomplete arrays of ORFs coding for proteins associated with mammalian pathogenicity, possibly involved in the occasional but often fatal cases of human C. violaceum infection. There is, in addition, a series of previously unknown but important enzymes and secondary metabolites including paraquat-inducible proteins, drug and heavy-metal-resistance proteins, multiple chitinases, and proteins for the detoxification of xenobiotics that may have biotechnological applications.
Keywords: bacterial enzyme; bacterial protein; carrier protein; chitinase; heavy metal; paraquat; adaptation; bacterial genome; biotechnology; cell motility; Chromobacterium; chromobacterium violaceum; detoxification; energy metabolism; gene sequence; membrane transport; nonhuman; nucleotide sequence; open reading frame; pathogenicity; priority journal; signal transduction; stress; xenobiotic metabolism; Adaptation, Physiological; Genome, Bacterial; Molecular Sequence Data; Open Reading Frames; Bacteria (microorganisms); Chromobacterium violaceum; Mammalia; Negibacteria; Prokaryota